PENINGKATAN KUALITAS KOMPETENSI ARBITER SYARI’AH DI BADAN ARBITRASE SYARI’AH NASIONAL (BASYARNAS) WILAYAH DIY - Fitriyanti, Fadia; Yunita, Ani; Hamsin, Muhammad Khaeruddin (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2020)
Enhancement of Sharia Arbitrators on Competence Quality in the Yogyakarta Special Region National Sharia Arbitration Board Abstract. The increase in cases resolved at the Yogyakarta Special Region National Sharia Arbitration Board (BASYARNAS DIY), the limitation of Islamic arbitrators, and the lack of expertise of arbitrators in dispute resolution raises issues related to the mastery of Sharia economic law for arbitrators in BASYARNAS DIY region. This community service program aims to increase the knowledge/ competence of expertise for Sharia arbiter in BASYARNAS DIY region, namely by conducting scientific discussions for Arbitrators as a basis for resolving Shariah economic disputes. The method of carrying out this dedication includes the preparation stage of scientific discussion, discussion on enhancing the competence of Sharia Arbitrators supported by pre-test and post-test during training and monitoring of evaluation activities as a reference for feedback for future discussion activities. This program was held on Friday July 26, 2019 in the meeting room of the Master of Law Degrees Program on the 2nd floor of the Postgraduate Building of Universitas Muhammadiyah Yogyakarta. The results of the community service activities were that the discussion went well and smoothly, attended by the BASYARNAS DIY Arbiter and internship students at the BASYARNAS DIY Region. With this discussion activity, the arbiter who previously did not understand about 50 percent related to the resolution of Islamic economic disputes to 100 percent really understood both materially and practically about the resolution of Islamic economic disputes delivered by speakers from the National Sharia Arbitration Board and the Indonesian National Arbitration Board so the arbiter's knowledge has increased significantly. Keywords: Enhancement, Competence, National Sharia Arbitration Board, Arbitrator. Abstrak. Meningkatnya perkara yang diselesaikan di BASYARNAS DIY, terbatasnya jumlah arbiter syari’ah, dan kurangnya keahlian arbiter dalam penyelesaian sengketa maka menimbulkan persoalan terkait penguasaan hukum ekonomi syari’ah bagi para arbiter di BASYARNAS wilayah DIY. Program pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan/kompetensi keahlian bagi arbiter syari’ah di BASYARNAS wilayah DIY yaitu dengan cara melakukan diskusi ilmiah bagi Arbiter sebagai dasar dalam menyelesaikan sengketa ekonomi syari’ah. Metode pelaksanaan pengabdian ini meliputi tahap persiapan diskusi ilmiah, diskusi peningkatan kompetensi Arbiter Syari’ah yang didukung dengan pre-test dan post-test pada saat pelatihan dan monitoring evaluasi kegiatan sebagai acuan feedback untuk pelaksanaan kegiatan diskusi kedepannya. Kegiatan pengabdian ini dilaksanakan pada hari jumat tanggal 26 Juli 2019 di ruang sidang Magister Ilmu Hukum di lantai 2 Gedung Pasca Sarjana Universitas Muhammadiyah Yogyakarta. Hasil kegiatan pengabdian ini ialah kegiatan diskusi berjalan dengan baik dan lancar dengan dihadiri oleh Arbiter BASYARNAS DIY dan mahasiswa magang di BASYARNAS Wilayah DIY. Dengan adanya kegiatan diskusi ini maka para arbiter yang sebelumnya kurang memahami sekitar 50 persen terkait penyelesaian sengketa ekonomi syari’ah menjadi 100 persen sangat memahami baik secara materi maupun praktik mengenai penyelesaian sengketa ekonomi syari’ah yang disampaikan oleh narasumber dari Badan Arbitrase Syari’ah Nasional Pusat dan Badan Arbitrase Nasional Indonesia sehingga pengetahuan arbiter mengalami peningkatan secara signifikan. Kata Kunci: Peningkatan, Kompetensi, BASYARNAS, Arbiter.